The Historical Dimensions of The Social Studies Education Curriculum In Indonesia - Erena Marsiana (Social Studies Conference Proceedings, 2021)
The curriculum in Indonesian education is constantly changing from time to time and is a breakthrough in education. The historical dimensions of the specific social studies education curriculum changed in 1945 as the national education curriculum underwent changes and continued in1974-1975, 1984-1990, 1994, 2004-2006, and 2013 to now. The historical dimension of Indonesia's social studies education curriculum is experiencing dynamics that are moving into a better realm. The integration of social studies is a result of the process of the dynamic level of the latest curriculum, for now, namely the 2013 curriculum as an improvement from the previous curriculum. This article describes the historical dimensions of Indonesia's social studies education curriculum, described through literature studies using search engines to obtain sources from ebooks and journals. The discussion that will be discussed in this article includes how the process of historical dimensions of the social studies education curriculum in Indonesia from time to time.